Immune platelet transfusion refractoriness in pediatric patients undergoing HSCT - Olivera Serbic; Zorana Andric; Svetlana Vojvodic; Dragomir Djokic; Marija Simic (Egyptian Pediatric Association Gazette)
Abstract Background Children who undergo hematopoietic stem cell transplantation (HSCT) sometimes have immune platelet transfusion refractoriness (IPTR). The thrombopoietin receptor agonist (TPO-RA) is used to increase platelet counts in a variety of immune thrombocytopenias. This study aims to explore the importance of anti-HLA class I antibodies (HLA-I-Abs) and antibodies against human platelet antigen (HPA-Abs) as causes of IPTR, their relationship with bleeding, and treatment options for IPTR. We observed 240 hemato-oncological pediatric patients who received platelet transfusions. IPTR was diagnosed on the basis of the corrected count increment (primary diagnostic criterion) and post-infusion percent platelet recovery. The HLA-I-Abs and HPA-Abs were identified via a Luminex assay, and suitable platelet donors for alloimmunized recipients were selected via a crossmatch or antibody specificity prediction strategy. Results Refractoriness was observed in 44 out of 240 (18.3%) patients. A total of 23 (9.58%) patients suffered from IPTR. HLA-I-Abs were detected in 5% of the patients, accounting for 82.6% of the IPTRs. HLA-I-Abs were present in 12 (52.2%) patients, 4 (17.4%) had HPA-Abs, and seven patients had both antibodies (29.5%). Autologous HSCT was a significant etiological factor for IPTR (OR 20.82, 95% CI 2.680–161.73; p = 0.004). Among the refractory patients, 13 (29.5%) experienced hemorrhagic complications. Two patients experienced heavy bleeding (8.6%). This was a consequence of IPTR, but also a nonimmune factor (p = 0.005). Refractory patients received more red blood cell transfusions, averaging 14.27 ± 13.45 units, compared with 6.97 ± 6.63 units in patients without refractoriness (p < 0.001). The number of buffy coat platelet concentrate units received was significantly greater in immune refractory patients (119.13 ± 140.33) than in nonimmune refractory patients (79.09 ± 113.63) (p = 0.025). Treatment with TPO-RAs significantly reduces the use of platelet transfusions. Conclusion Even post-transplant pediatric patients can produce HLA-I-Abs and HPA-Abs. HLA-I-Ab was identified as the most prevalent independent factor of IPTR. Patients with IPTR presented lower pretransfusion platelet counts, experienced more bleeding events, and received more platelet concentrates than other refractory patients did. Filtered and irradiated HLA-matched apheresis units of platelet concentrate are recommended to support these patients. We emphasize the potential positive impact of synthetic thrombopoietin receptor agonists in IPTR patient care and for future research.